Faktor yang Mempengaruhi Bidan dalam Inisiasi Laktasi di Klinik Bersalin Kota Banda Aceh Nanggroe Aceh Darussalam - Husnah Husnah; Detty Siti Nurdiati; Emy Huriyati (Alma Ata University Press, 2014)
Breastfeeding is recommended soon or 30 minutes to an hour after childbirth. Breastfeeding or initiation of lactation will affect successful continuity of breast milk supply and prevent infant morbidity and mortality caused by infection. However, some studies convey that the prevalence of lactation initiation is still relatively low due to factors of mothers and midwives who assist childbirth. This was a quantitative observational study with cross sectional design aimed to identify the effect of knowledge, attitude, behavior and duration of occupation of midwives to lactation initiation at maternity clinic of Banda Aceh Municipality. Qualitative data were obtained through indepth interview. Samples were purposively chosen from all midwives working at maternity clinic of Banda Aceh Municipality. Data analysis used univariable, bivariable with Chi square and multivariable with logistic regression. The result of bivariable analysis showed that knowledge and behavior of midwives affected lactation initiation (p<0.05) whereas variable of attitude and duration of midwives’ occupation did not affect lactation initiation. The result of multivariable analysis showed that knowledge and behavior of midwives affected lactation initiation (p=0,041 OR= 3,94 (95%-Cl:1.05–14.69) and (p=0,016 OR=4,52 (95%-Cl:1.32 – 15.46). In conclusion, variables of knowledge and behavior of midwives affected lactation initiation whereas variable of attitude and duration of midwives’ occupation did not affect lactation initiation.